Child fostering and the educational outcomes of Jamaican children. (November 2021) - Bose-Duker, Theophiline; Henry, Michael; Strobl, Eric
Highlights: Informal fostering is prevalent in the developing world. We use panel data for Jamaica to examine the impact of fostering on school attendance. A conditional transfer programme increases school absence for fostering children in Jamaica. Abstract: The practice of informal fostering is prevalent in many developing regions of the world. Our paper investigates the effects of this practice on school attendance in Jamaica using a rotating panel data set of children constructed from the 2004, 2006, 2007, 2008, 2009, and 2010 rounds of the Jamaican Survey of Living Conditions. Using panel data allows us to deal more effectively with the problem of endogeneity by being able to control for household and child fixed effects. Our findings indicate that the effect of fostering on school attendance depends on whether the household is a beneficiary of PATH, a conditional cash transfer programme instituted by the Government of Jamaica in 2001. We find that a foster child that lives within a non-PATH household is associated with being less likely to be absent from school than a foster child who lives in a household that benefits from PATH. This is true especially for foster girls. Although the PATH programme generally appears to be linked to the improvement in school attendance of Jamaican children, the benefits of the programme may be skewed towards biological children.